Development and validation of a vaccine hesitancy scale for COVID-19 to the Portuguese language (Research, Society and Development, 2023)
This is a psychometric study aimed at developing and validating a specific scale that assesses the vaccine hesitancy behavior of COVID-19 to the Portuguese language. The vaccine hesitancy scale for COVID-19 vaccines was developed in Brazil based on the Vaccine Hesitancy Scale developed by the Strategic Advisory Group of Experts on Immunization Working Group. Data were collected at the end of the first wave of the COVID-19 pandemic in Brazil (between March 1 and June 30 of 2021) by convenience sampling and snowballing using electronic surveys with 1345 participants. We carried out an exploratory factorial analysis (EFA) and confirmatory factorial analysis (CFA) of 10 items. Our findings for the EFA suggested only a single dimension and the unidimensional congruence of 0.95 and explained a common variance of 0.90; all items presented a significant factor loading (≥ 0.30) with excellent reliability (Cronbach’s alpha of 0.88). The CFA showed the model fit indices were satisfactory (x2 = 66.0538, gl = 35, p = 0.001; RMSEA = 0.03 CI [0.02;0.04]); CFI = 0.98; TLI = 0.98) with the factor loadings cut-off ranging from 0.32 to 0.88. Our findings revealed that the vaccinal hesitancy assessment tool for COVID-19 vaccines in the Portuguese language has evidence of internal validity and reliability, and it is best represented as a unifactorial 10-item structure yielding a total score.